ANALISIS PENGARUH KEBIJAKAN MONETER TERHADAP RETURN INDEKS SAHAM INFOBANK15 DI INDONESIA PERIODE NOVEMBER 2012- FEBRUARI 2016 (STUDY KASUS PADA INDEKS SAHAM PERBANKAN INFOBANK15 YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Eva Yudika Sembiring (Quantitative Economics Journal, 2017)
This study was aimed to see the effects of of monetary policy on Infobank15 index return listed on the Indonesia Stock Exchange. Monetary policy variables is proxied through BI rate, followed by inflation and exchange rate, as well as the Dow Jones index as a control variable. The method of data analysis was multiple regression analysis using secondary data from November 2012 to February 2016. The results showed that the BI rate, inflation, exchange rate, and the Dow Jones index significantly take effect to on Infobank15 index return. The coefficient of determination equals to 0.73 which means that 73% of Infobank15 index returns can be explained by BI Rate, Inflation, exchange rate, and the Dow Jones Index while the rest (27%) is explained by other variables outside of the regression model.